2020
DOI: 10.1093/cid/ciaa216
|View full text |Cite
|
Sign up to set email alerts
|

Critical National Shortage of Cefazolin in Japan: Management Strategies

Abstract: The shortage of antimicrobials poses a global health threat. In Japan, for instance, the current, critical shortage of cefazolin, a first-line agent for the treatment of common infectious diseases and surgical antimicrobial prophylaxis, has had a substantial impact on inpatient care. A shortage of essential antimicrobial agents like cefazolin leads to increased consumption of alternative antimicrobial agents with broad-spectrum activity, with the unintended consequence of militating against antimicrobial stewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…In low-income countries, literature cited medicines used for TB, Malaria, and HIV due to the increased incidence of these diseases and the unavailability of essential drugs rather than drug shortages or stock-out. Table 1 shows the medicines affected by shortages in different countries (Elbagir et al, 1995;Kangwana et al, 2009;Tren et al, 2009;Ballinger, 2010;Ventola, 2011;Griffith et al, 2012;Liang and Mackey, 2012;Malik et al, 2013;Quilty, 2014;Ricci et al, 2016;Donohue and Angus, 2017;Gross et al, 2017;Hsueh et al, 2017;Meloni et al, 2017;Tan et al, 2017;Vail et al, 2017;Banerjee et al, 2018;Dave et al, 2018;Gundlapalli et al, 2018;Holcombe et al, 2018;Said et al, 2018;Benge and Burka, 2019;Visage et al, 2019;Yellapu et al, 2019;Benhabib et al, 2020;Choo and Rajkumar, 2020;Clark et al, 2020;Honda et al, 2020;Siow et al, 2020;Sun et al, 2020;Mclaughlin et al, 2017;Dave et al, 2018).…”
Section: Drugs Reported In Shortagementioning
confidence: 99%
“…In low-income countries, literature cited medicines used for TB, Malaria, and HIV due to the increased incidence of these diseases and the unavailability of essential drugs rather than drug shortages or stock-out. Table 1 shows the medicines affected by shortages in different countries (Elbagir et al, 1995;Kangwana et al, 2009;Tren et al, 2009;Ballinger, 2010;Ventola, 2011;Griffith et al, 2012;Liang and Mackey, 2012;Malik et al, 2013;Quilty, 2014;Ricci et al, 2016;Donohue and Angus, 2017;Gross et al, 2017;Hsueh et al, 2017;Meloni et al, 2017;Tan et al, 2017;Vail et al, 2017;Banerjee et al, 2018;Dave et al, 2018;Gundlapalli et al, 2018;Holcombe et al, 2018;Said et al, 2018;Benge and Burka, 2019;Visage et al, 2019;Yellapu et al, 2019;Benhabib et al, 2020;Choo and Rajkumar, 2020;Clark et al, 2020;Honda et al, 2020;Siow et al, 2020;Sun et al, 2020;Mclaughlin et al, 2017;Dave et al, 2018).…”
Section: Drugs Reported In Shortagementioning
confidence: 99%
“…The actual DID values of the government-recommended alternatives ceftriaxone, flomoxef, clindamycin, and cefotiam were higher than their predicted DID values. It was suggested that drug makers increased the production of these drugs to alleviate damage caused by the cefazolin shortage; however, the production increases were insufficient to compensate for the cefazolin shortage, which led to secondary shortages among these drugs [ 19 ]. According to a questionnaire-based study, the cefazolin shortage caused considerable damage in the maintenance of quality-assured medicines in various hospitals [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Ministry of Health, Labour and Welfare of Japan published a list of alternative antimicrobials to cefazolin [ 17 ]; however, this caused secondary shortages among the alternative drugs [ 18 ]. Collapse of antimicrobial stewardship due to the cefazolin shortage has already been reported by a single center, and demonstrated the rapid increase in the use of third-generation cephalosporins after the cefazolin supply became limited [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The actual DID values of the government-recommended alternatives ceftriaxone, omoxef, clindamycin, and cefotiam were higher than their predicted DID values. It was suggested that drug makers increased the production of these drugs to alleviate damage caused by the cefazolin shortage; however, the production increases were insu cient to compensate for the cefazolin shortage, which led to secondary shortages among these drugs [21]. According to a questionnaire-based study, the cefazolin shortage caused considerable damage in the maintenance of quality-assured medicines in various hospitals [22].…”
Section: Discussionmentioning
confidence: 99%